Effects of dietary fibre and tea catechin, ingredients of the Japanese diet, on quol production and bone mineral density in isoflavone-treated ovariectomised mice - Tousen Y; Uehara M; Kruger MC; Ishimi Y (Cambridge University Press, 2012)
Equol is a metabolite of the isoflavone daidzein (Dz) and is produced by the bacterial microflora in the distal intestine and colon. Some epidemiological studies have reported an association between increased equol production and intakes of green tea or dietary fibre, which are ingredients of the standard Japanese diet. We examined the effects of a diet supplemented with Dz and tea catechin or dietary fibre on equol production and bone mineral density in ovariectomised (OVX) mice. Female mice of the ddY strain were either sham operated or OVX. OVX mice were fed a control diet, a 0·1 % Dz-supplemented diet or a 0·1 % Dz diet supplemented with one of the food components commonly consumed in the Japanese diet. The mice were given 1 % tea catechin (w/w) as part of the diet in Expt 1 or 5 % polydextrose (PD) and 5 % raffinose (Raf) (w/w) as part of the diet in Expt 2. Catechin reduced serum equol levels and attenuated the beneficial effect of Dz on femoral bone loss. The soluble dietary fibres PD and Raf stimulated equol production, and enhanced the bone-protective effects of Dz on femoral bone. These results suggest that dietary fibre, in particular, PD, may alter the bioavailability of isoflavones and prevent osteopenia in OVX mice.
Creative Commons Attribution Non-Commercial Share Alike 2.5 License
Keywords: BMD, bone mineral density; Dietary fibre; Dz, daidzein; EGCG, epigallocatechin gallate; Equol; Japanese diet; OVX, ovariectomised; PD, polydextrose; Raf, raffinose; Soya isoflavones; 1111 Nutrition and Dietetics